Effects of preweaning and postweaning implants on suckling, growing, and finishing steer performance - a three trial summary - Simms, D.D.; Goehring, T.B.; Lee, R.W.; Brandt, Robert T., Jr.; Laudert, S.B.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Over 500 crossbred steers were used in three trials to compare lifetime implant strategies and to study the effects of implanting during the suckling period on performance in the growing and finishing periods. Contrary to previous research, implanting in the suckling period did not increase suckling gain. Implanting in the growing period increased (P<.05) average daily gain, and the implant response in the growing period was not influenced by suckling implant treatment. Steers implanted twice during the finishing period had similar finishing gains regardless of prior implant treatment. Steers implanted only once during the finishing phase gained less (P<.05) than those implanted twice, and while their gains were higher than those of control steers, the difference was small (P>.05). Implanting steers in the finishing phase tended to improve feed conversion but again the difference was not statistically significant. All implant treatments increased (P<.05) lifetime average daily gains and total gain, and there was no difference among implant combinations. Implant treatments increased lifetime gains by 30 to 54 lbs. Because implanting in the suckling period did not reduce cattle performance during the growing and finishing periods, there appears to be no basis for discounting the price of previously implanted cattle. Additionally, this study emphasizes the importance of reimplanting cattle during long finishing periods
Keywords: Beef; Preweaning; Postweaning; Implants; Suckling; Growing; Performance